(untitled) (Revista de Estudos da Linguagem, 2024)
This work performs a comparative analysis of two episodes of our political history that suggest the existence of a certain regularity in the way media instances responsible for the circulation of political discourse coordinate themselves today. Given the similarity of the linkages formed between such instances and the consequences generated in each case, the research aim was the analysis of the circuit that interconnects them, with which a series of responses seem to coordinate themselves and stabilize a sort of chain communication mechanism. To build our analytical path, the concepts of genre chain (Swales, 2004), which serves the purpose of investigating how discursive genres are associated, and mediatic linkage (Primo, 2008), with which one must assume that the different media levels function in an articulated way supported by intertextual mechanisms, were combined. Through the analysis of the resumption strategies used in each of the communicational instances, the analysis displayed that, in the examined chain, the TV exerts a centralizing role insofar as it provides the initial motion that generates the circuit in which genres appear juxtaposed, always recovering the television content. From this initial stimulus, episodes are critically commented on in social media (notably on Twitter), which leads to the representation of this repercussion in digital newspapers, and, finally, in political acts and manifestations in the streets.